CAUSES AND FACTORS OF VIRTUALIZATION IN THE LIFE OF YOUTH - Yusupov Samandar (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the virtual world, the impact of virtual education on the socio-political and economic life of young people. In addition, the reasons and factors for the development of media use in the context of globalization and ways to use them wisely are discussed. The work carried out in our country in this direction, the reforms being carried out to ensure the effective form of virtualization will be described